Measuring, monitoring & recording on track delegate information : Tuesday 2 July at One Great George Street Conference Centre, the Institution of Civil Engineers, London (Thomas Telford, 1996)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in July 1996.
Keywords: Railroads -- Measurement -- Congresses.; elektronické knihy; electronic books